2017
DOI: 10.1007/s11596-017-1688-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with trait anger level of juvenile offenders in Hubei province: A binary logistic regression analysis

Abstract: The risk factors of high trait anger of juvenile offenders were explored through questionnaire study in a youth correctional facility of Hubei province, China. A total of 1090 juvenile offenders in Hubei province were investigated by self-compiled social-demographic questionnaire, Childhood Trauma Questionnaire (CTQ), and State-Trait Anger Expression Inventory-II (STAXI-II). The risk factors were analyzed by chi-square tests, correlation analysis, and binary logistic regression analysis with SPSS 19.0. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Hence, neglect may lead to disorganized attachment, rejection sensitivity, and impaired emotion regulation, 51 which is linked to symptoms of borderline personality disorder (BPD), among others 52 . The negative impact of emotional abuse and neglect on anger was also found in previous studies 11–13,21 . While neglect may result in difficulties in the regulation of emotions, physical abuse may result in hypervigilance to threat.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Hence, neglect may lead to disorganized attachment, rejection sensitivity, and impaired emotion regulation, 51 which is linked to symptoms of borderline personality disorder (BPD), among others 52 . The negative impact of emotional abuse and neglect on anger was also found in previous studies 11–13,21 . While neglect may result in difficulties in the regulation of emotions, physical abuse may result in hypervigilance to threat.…”
Section: Discussionmentioning
confidence: 93%
“…Cross‐sectional studies that took into account a broad spectrum of childhood adversities found significant associations between CT, on the one hand, and anger in adulthood, on the other hand, including a dose–response relationship 11–14 . To identify predictors of anger, it is relevant to distinguish the subjective experience and the (physical) expression of anger 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, a further complicating issue is that subjects who develop mood disorders are often victims of sexual/physical abuse and parental neglect during childhood [16]. Such traumatic experiences have been associated, on one hand, to anger and irritability [17,18]; on the other, to suicidal ideation and behavior [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Van Smeden et al (2016) have used BLR in medical research. Tang et al (2017) have investigated risk factors of high trait anger of juvenile offenders by using BLR. Kanbayashi et al (2017) applied BLR for identifying and forecasting the risk factors for Varicella Zoster and Post Herpetic Neuralgia (PHN) after Hematopoietic Stem Cell Transplantation (HSCT).…”
Section: Introductionmentioning
confidence: 99%